Dietary partitioning promotes the coexistence of planktivorous species on coral reefs. Issue 10 (13th May 2019) - Leray, Matthieu; Alldredge, Alice L.; Yang, Joy Y.; Meyer, Christopher P.; Holbrook, Sally J.; Schmitt, Russell J.; Knowlton, Nancy; Brooks, Andrew J.
Abstract: Theories involving niche diversification to explain high levels of tropical diversity propose that species are more likely to co‐occur if they partition at least one dimension of their ecological niche space. Yet, numerous species appear to have widely overlapping niches based upon broad categorizations of resource use or functional traits. In particular, the extent to which food partitioning contributes to species coexistence in hyperdiverse tropical ecosystems remains unresolved. Here, we use a molecular approach to investigate inter‐ and intraspecific dietary partitioning between two species of damselfish ( Dascyllus flavicaudus, Chromis viridis ) that commonly co‐occur in branching corals. Species‐level identification of their diverse zooplankton prey revealed significant differences in diet composition between species despite their seemingly similar feeding strategies. Dascyllus exhibited a more diverse diet than Chromis, whereas Chromis tended to select larger prey items. A large calanoid copepod, Labidocera sp., found in low density and higher in the water column during the day, explained more than 19% of the variation in dietary composition between Dascyllus and Chromis . Dascyllus did not significantly shift its diet in the presence of Chromis, which suggests intrinsic differences in feeding behaviour. Finally, prey composition significantly shifted during the ontogeny of both fish species. Our findings show that levels of dietary specialization among coral reef associated species have likely been underestimated, and they underscore the importance of characterizing trophic webs in tropical ecosystems at higher levels of taxonomic resolution. They also suggest that niche redundancy may not be as common as previously thought.